Process plant design - Smith, Robin; John Wiley & Sons (Hoboken, NJ : Wiley, 2024)
'This book is intended to provide a practical guide to chemical engineering process plant design for students of chemical engineering, particularly in relation to design projects. It will also be of practical value to practising chemical engineers. It picks up the design process after the texts on conceptual process design and covers an area which is critically important to chemical engineers. The text starts by giving an up-to-date approach to the structure of process design projects as practised industrially. After a summary of the conceptual development process designs, the text explores the wider issues of process design in terms of the services (utilities) required to make a practical process design function. A key learning requirement for all chemical engineering students is gaining an understanding of reliability, maintainability and availability. Without knowledge of this area, chemical engineers cannot specify with confidence the use of standby equipment, redundancy, the reliability required of safety equipment, the required availability to meet production targets and the use of storage to achieve the required process availability. A number of chapters have been included to give an introduction to reliability theory to achieve these goals'--
Includes index.
Keywords: Chemical plants -- Design and construction; Chemical process control